POLUSI ASAP PLASTIK DALAM PERSPEKTIF HADIS: ANALISIS MAQĀṢID AL-SYARĪ’AH TERHADAP KRISIS EKOLOGI MODERN: PLASTIC SMOKE POLLUTION IN THE PERSPECTIVE OF HADITH: A MAQĀṢID AL-SHARĪʿAH ANALYSIS OF THE MODERN ECOLOGICAL CRISIS - Abd. Bashir Fatmal; La Ode Ismail Ahmad; Darsul S Puyu; Muhammad Yahya (LPPM Institut Daarul Qur'an Jakarta, Indonesia, 2025)
The ecological crisis caused by plastic waste has evolved into a global issue, particularly through air pollution resulting from open burning, which poses serious threats to human health and environmental sustainability. This study analyzes the phenomenon of plastic smoke pollution from the perspective of hadith using a maqāṣid al-sharī‘ah approach. The hadith prohibiting harm to oneself and others (lā ḍarar wa lā ḍirār) and the prohibition of isrāf (excessiveness) serve as the normative foundation for assessing the ecological and ethical dangers of plastic burning practices. The method employed is library research, examining relevant hadiths, classical and contemporary commentaries (sharḥ), as well as modern scientific studies on plastic pollution. The findings indicate that these hadiths not only regulate social ethics but also embody ecological principles that support sustainability agendas. The maqāṣid analysis affirms that burning plastic violates the principles of ḥifẓ al-nafs (protection of life), ḥifẓ al-nasl (protection of progeny), ḥifẓ al-māl (protection of property), and ḥifẓ al-bī’ah (protection of the environment). This research contributes to the development of Islamic environmental ethics by offering a normative framework that can serve as a foundation for regulations, fatwas, and public policies in addressing the modern ecological crisis.